2009
DOI: 10.1097/01.won.0000347655.56851.04
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Interventions to Reduce the Risk of Catheter-Associated Urinary Tract Infection

Abstract: Evidence from parts 1 and 2 of this Evidence-Based Report Card provides a sound basis for designing an evidence-based program to prevent CAUTI. Essential elements of a CAUTI prevention program include staff education, ongoing monitoring of CAUTI incidence, monitoring catheter insertion and ensuring prompt removal, and careful attention to techniques for catheterization and catheter care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 48 publications
1
79
0
14
Order By: Relevance
“…Several resources suggest that the catheter insertion site be cleaned with soap and water daily when bathing or showering [10,11] .…”
Section: Perineal Hygienementioning
confidence: 99%
“…Several resources suggest that the catheter insertion site be cleaned with soap and water daily when bathing or showering [10,11] .…”
Section: Perineal Hygienementioning
confidence: 99%
“…108,118 Part of the challenge is defining sterile and aseptic technique within the clinical context of the skill. 121 Willson and colleagues 120 conducted a review of the literature and found that aseptic technique for urinary catheter placement was most often defined as the use of sterile gloves, mask, sterile barriers, perineal washing using an antiseptic cleanser, and no-touch insertion technique. Current recommendations suggest that maintaining aseptic technique and using sterile equipment while inserting the catheter are both important elements to minimize infection.…”
Section: Nursing Interventions To Prevent Catheter-associated Urinarymentioning
confidence: 99%
“…Research on meatal care with antiseptic cleansers, creams, lotions, or ointments found them to be to be no better than routine perineal care provided with soap and water at reducing CaUTIs. 106,118,[120][121][122]124 Some evidence suggests that antiseptic agents may actually increase the risk of infection by irritating the urethral meatus. 120 Current guidelines suggest "routine hygiene" (eg, cleansing of the meatal surface during daily bathing) is all that is needed to maintain an indwelling urinary catheter.…”
Section: Nursing Interventions To Prevent Catheter-associated Urinarymentioning
confidence: 99%
See 1 more Smart Citation
“…O traumatismo uretral pode ser minimizado através de medidas simples, todavia de grande impacto, representadas pelo uso de lubrificantes, escolha e manuseio de materiais adequados para a introdução e fixação do cateter, além de cuidados com o balonete (MIRANDA et al, 2006;NEWMAN 2007;LEUCK et al, 2012 (DEVINE, 2003;AARONSO et al, 2008;GRAY, 2008;KASHEFI et al, 2008;TZORTZIS et al, 2009;WILLSON et al, 2009;FAKIH et al, 2010;GORDETSKY et al, 2011 (TANABE et al, 2004), de 0,5 a 2 ml e cerca de 2 a 3 minutos em lactentes e 0,5 a 2 ml e cerca de 10 minutos em crianças acima de um ano (GERARD et al, 2003;VAUGHAN et al, 2005).…”
Section: Trauma Uretralunclassified